Copper‐Free Postsynthetic Labeling of Nucleic Acids by Means of Bioorthogonal Reactions. Issue 11 (2nd July 2015) - Merkel, Marcus; Peewasan, Krisana; Arndt, Stefanie; Ploschik, Damian; Wagenknecht, Hans‐Achim
Abstract Postsynthetic modification of nucleic acids has the advantage that the chemical development of only a few building blocks is necessary, each bearing a chosen reactive functional group that is applicable to its reactive counterpart for a variety of different labeling types. The reactive group is either linked to phosphoramidites for chemical synthesis on solid phase or attached to nucleoside triphosphates for application in primer extension experiments and PCR. Chemoselectivity is required for this strategy, together with bioorthogonality to perform these labelings in living cells or even organisms. Currently, the copper‐free reactions include strain‐promoted 1, 3‐dipolar cycloadditions, "photoclick" reactions, Diels–Alder reactions with inverse electron demand, and nucleophilic additions. The majority of these modification strategies show good to excellent reaction kinetics, an important prerequisite for labeling inside cells and in vivo in order to keep the concentrations of the reacting partners as low as possible.